Bentuk Tes Kemahiran Berbicara Bahasa Arab (Tingkat Dasar, Menengah dan Lanjutan) - Enramika, Tomi (Islamic Education, 2022)
This study aims to examine the forms of speaking skill tests in Arabic at basic, intermediate, and advanced levels. This research is important for providing effective and comprehensive evaluation tools to measure Arabic speaking skills. The method used is descriptive analysis, collecting data from academic journals, textbooks, and previous research reports. Additionally, this study involves case studies of existing speaking skill tests, both in educational institutions and in certification exams. Data analysis is conducted to identify the main characteristics of each level of speaking proficiency. At the basic level, the focus is on the ability to pronounce simple words and phrases and understand basic conversations. At the intermediate level, the analysis focuses on the ability to form complex sentences and participate in longer conversations. At the advanced level, the evaluation is directed at the ability to convey ideas clearly and logically. The components evaluated include fluency, grammatical accuracy, vocabulary, and the ability to understand and respond. The results of this research are expected to provide guidance for developing speaking skill tests that better meet the needs of Arabic language learning at various levels.